E-Commerce Logistic and Supply Chain Management: Evidence from Indonesian Perspectives - Nik Khadijah Nik Abdul Rahman; Salzainna Zainul Abidin; Gholam Reza Zandi; Mohammad Amin; Nira Hariyatie Hartani (International Journal of Supply Chain Management, 2018)
The web is essentially affecting how firms cooperate with one another and their clienteles. Past interruptions for supply chain incorporation, for example, high exchange prices between allies, weak info accessibility, with encounters of overseeing multifaceted borders between utilitarian affiliations have been on the whole dissolving on the web. In this study, it is examined how the web has been altering SCM. 100 Questionnaire has been used to acquire the response from the employees of Indonesia companies having E-Commerce business. Smart PLS software has been used to get data examination. ponder presented a study of developing on the consequence of e-business on SCM with descriptive frameworks, e-procurement, e-collaboration and e-commerce.